Application of Fuzzy - AHP - Topsis Model Integration to Select Green C2C Websites in Online Shopping - Dung, Tran Trung (International Journal of Scientific Research and Management (IJSRM), 2024)
In today's digital age, online shopping has become an indispensable part of daily life. The strong development of e-commerce platforms helps consumers easily search and choose products from around the world with just a few clicks. Making purchasing decisions is not simple when buyers have to consider many factors such as price, quality, brand and many other factors. To support smart consumers in shopping, the study applied the Fuzzy - AHP - Topsis integrated model to evaluate purchasing criteria on 4 popular C2C websites: Shopee, Tiki, Lazada and Sendo.